Precision Interface Engineering of an Atomic Layer in Bulk Bi2Te3 Alloys for High Thermoelectric Performance - Kim, Kwang-Chon; Lim, Sang-Soon; Lee, Seung Hwan; Hong, Junpyo; Cho, Deok-Yong; Mohamed, Ahmed Yousef; Koo, Chong Min; Baek, Seung-Hyub; Kim, Jin-Sang; Kim, Seong Keun (AMER CHEMICAL SOC, 2019)
Grafting nanotechnology on thermoelectric materials leads to significant advances in their performance. Creation of structural defects including nano-inclusion and interfaces via nanostructuring achieves higher thermoelectric efficiencies. However, it is still challenging to optimize the nanostructure via conventional fabrication techniques. The thermal instability of nanostructures remains an issue in the reproducibility of fabrication processes and long-term stability during operation. This work presents a versatile strategy to create numerous interfaces in a thermoelectric material via an atomic-layer deposition (ALD) technique. An extremely thin ZnO layer was conformally formed via ALD over the Bi0.4Sb1.6Te3 powders, and numerous heterogeneous interfaces were generated from the formation of Bi0.4Sb1.6Te3-ZnO core-shell structures even after high-temperature sintering. The incorporation of ALD-grown ZnO into the Bi0.4Sb1.6Te3 matrix blocks phonon propagation and also provides tunability in electronic carrier density via impurity doping at the heterogeneous grain boundaries. The exquisite control in the ALD cycles provides a high thermoelectric performance of zT = 1.50 +/- 0.15 (at 329-360 K). Specifically, ALD is an industry compatible technique that allows uniform and conformal coating over large quantities of powders. The study is promising in terms of the mass production of nanostructured thermoelectric materials with considerable improvements in performance via an industry compatible and reproducible route.
Keywords: BISMUTH-ANTIMONY TELLURIDE; ENHANCEMENT; ZT